2009
DOI: 10.1002/qj.399
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and evolution of cold‐frontal misocyclones

Abstract: A numerical simulation of an intense, narrow cold-frontal rain band (NCFR) is presented. This front was associated with localized wind damage as it moved eastwards across the United Kingdom on 24 September 2007. The model used was the operational and research Weather Research and Forecasting-Advanced Research (WRF-ARW) mesoscale model, initialized with Global Forecast System (GFS) operational model output data. The simulation produced a front strongly resembling that seen in radar imagery and conforming to pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 39 publications
(47 reference statements)
4
27
0
Order By: Relevance
“…The association of tornadoes to frontal waves has been considered in recent studies (Clark, 2008;Smart and Browning, 2009;Groenemeijer et al, 2010). Markowski et al (1998) found that nearly 70 % of tornadoes during the Verification of the Origins of Rotation in Tornadoes EXperiment (VORTEX) occurred near a pre-existing baroclinic boundary, most of them within 30 km distance on its cold side.…”
Section: Seasonal Composite Anomalies Of Synoptic Conditions and Liftmentioning
confidence: 99%
“…The association of tornadoes to frontal waves has been considered in recent studies (Clark, 2008;Smart and Browning, 2009;Groenemeijer et al, 2010). Markowski et al (1998) found that nearly 70 % of tornadoes during the Verification of the Origins of Rotation in Tornadoes EXperiment (VORTEX) occurred near a pre-existing baroclinic boundary, most of them within 30 km distance on its cold side.…”
Section: Seasonal Composite Anomalies Of Synoptic Conditions and Liftmentioning
confidence: 99%
“…Microscale studies of fronts have revealed numerous features that are not observed at mesoscales; for example, Doswell and Haugland (2007) found that the temperature increased after the passage of a nocturnal cold front because of the destruction of an inversion, which permitted warm air from aloft to be mixed to the surface by turbulence behind the leading edge of the front. Many other investigators have also noted the visual similarity between certain synoptic-scale cold fronts and laboratory density currents (e.g., Young and Johnson 1984;Friedrich et al 2008;Smart and Browning 2009), and a summary of the relationship between cold fronts and density currents is given by Smith and Reeder (1988). Shapiro (1984) presented instrumented mast observations of a dry cold front passage in Colorado that showed that the temperature decrease of 138C was confined within a 200-m-wide zone.…”
Section: Introductionmentioning
confidence: 99%
“…The PCs are typically aligned at a clockwise angle with respect to the synoptic-scale cold front (e.g., Hobbs and Persson 1982;Parsons and Hobbs 1983a;Wakimoto and Bosart 2000). Horizontal shear instabilities (HSIs) along the leading edge of a cold front or their coupling with a convective instability have frequently been proposed as mechanisms that lead to the alongfront variability (AFV) of NCFRs (e.g., Matejka 1980;Hobbs and Persson 1982;Moore 1985, Carbone 1982Parsons and Hobbs 1983b;Wakimoto and Bosart 2000;Smart and Browning 2009).…”
Section: Introductionmentioning
confidence: 99%